Study of drug prescription pattern in ischemic heart disease patients - Sawant, Mahadeo P.; Padwal, Sudhir L.; Jadhav, Rakesh R.; Pise, Harshal N.; Shinde, Rucha (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drug utilization pattern studies helps to screen, assess and propose appropriate modifications in prescription practices, this would help to make patient care rational and cost effective. Study was intended to analyse the drug prescribing pattern for treatment of Ischemic heart disease using WHO indicators. Methods: This is a cross sectional observational study conducted on ischemic heart disease patients admitted at inpatient department of medicine in a tertiary care teaching hospital. The study consisted of analysis of drug utilization pattern of prescribed drugs. Results: IHD was more commonly seen in males (70.06%) than females (29.94%). IHD was most commonly seen in patients of age group of 61-70 year. Drugs prescribed to patients belong to various therapeutic classes ranging from anti-platelets, anticoagulants, anti-anginal, antithrombin, thrombolytic, hypolipidemics. The most commonly prescribed therapeutic class of drugs was antiplatelet (86.26%) followed by hypolipidemic (82.25%) and ACE inhibitors drugs (46.60%). Average number of drugs per encounter was 7.70. Drugs were prescribed by their generic names were 29.99%. Out of total study group 22.06% patients were prescribed at least one antibiotic. Injections were prescribed only in 1392 (27.86%) out of 4995 drugs. Of total drugs 3270 (65.45%) of drugs were from National List of Essential Medicines-2016 (NLEM -2016) and 2774 (55.53%) drugs prescribed were from WHO-EML-2016. Conclusions: Risk of artery disease increased with increasing age. IHD was more common in males than females. The most commonly prescribed drug classes in Ischemic heart disease were anti-platelet drugs followed by hypolipidemic agents.